Застосування економіко-математичних методів у дослідженні конкурентоспроможності підприємств - Власюк, Ю. О.; Педченко, Анна Павлівна; Педченко, Анна Павловна; Pedchenko, Hanna (Мелітополь: ТДАТУ, 2017)
UK: В статті доведено, що наявність розвиненої методики оцінки конкурентного середовища підприємства підвищує здатність зацікавлених сторін комплексно та якісно аналізувати ринкову ситуацію і визначати перспективи розвитку досліджуваного підприємства. Крім цього, розглянуто основні властивості категорії “конкурентоспроможність підприємства”, наведено етапи її аналізу. Обгрунтовано доцільність та узагальнено особливості застосування економіко-математичних методів у дослідженні конкурентоспроможності підприємства. EN: Under competitive environment, any entity should assess its own level of competitiveness for the effective functioning and assessment of prospects for the future. Decision-making on choosing the ways of enterprise development is based on the information that obtained as a result of its internal and external setting assessment. The purpose of the article is to systematize economic and mathematical methods that can be used to assessing the level of enterprise competitiveness. Currently, entity for the effective functioning and evaluation of its future prospects should analyze and facilitate the enhancement of competitiveness. Taking into account the scale of analysis, the existence of a large number of specific methods for researching of enterprises competitiveness, problems arising during the collection and processing of initial information, we consider that it is appropriate to apply at certain stages of the study mathematical methods and models. According to the results of the analysis of recent studies and publications, the main economic and mathematical methods that can be applied in the research of the competitiveness of enterprises have been summarized. Their main advantages and disadvantages have been given. The tasks being able to be performed using the above mentioned methods has been considered. It can be concluded, that the use of statistical and economicamathematical methods in assessing the competitiveness of the enterprise and in shaping its strategy allows to analyze economic objects and processes, to forecast the development of economic processes, support the adoption of managerial decisions at all levels of the economic management hierarchy. The symbiosis of special and mathematical research methods can increase the accuracy and efficiency of the use of the former, and the development of information technology, the emergence and widespread use of applications greatly simplify the use of the latter.
The application of economic and mathematical methods in assessing of enterprises сompetitiveness
Keywords: конкурентоспроможність підприємства; фактори конкурентоспроможності; система показників; економіко-математичні методи; математичне моделювання; enterprise competitiveness; competitiveness factors; indicators system; economic and mathematical methods; modeling